Dimensi Partisi Graf Hasil Amalgamasi Siklus - Hasmawati Hasmawati; Ahmad Syukur Daming; Loeky Haryanto; Budi Nurwahyu (Department of Mathematics, Hasanuddin University, 2020)
Let be a connected graph G and -partition of end . The coordinat to is definition . If for every two vertices in t , then is a called k-resolving partition of . The minimum k such that is a k-resolving partition of is the partition dimension of and denoted by . In this paper, we show that the partition dimension for amlagamation of cycle graph for To proof this results, we was used mathematical induction method.